Manfaat Penyuluhan Tentang Menarche Terhadap Peningkatan Pengetahuan Siswi Sekolah Dasar Negeri 2 Tanjung Benoa - Putu Anna Artha Rahayu; Ni Nyoman Budiani; Ni Wayan Armini (Poltekkes Kemenkes Denpasar, 2018)
Menstruating important events in the life of women, menstruation becomes a sign of a woman ready to perform reproductive functions. Young women need information about menstruation. The purpose of this research is to know the benefit counseling about menarche to the knowledge of female students at SDN 2 Tanjung Benoa 2018. This design of research was a pre-experimental one-group pretest-posttest design, measurements were carried out before and after treatment. The difference in the two results is considered a treatment effect. The respondents of this study were 56 elementary school students. Data analysis using the Wilcoxon test, with the help of a computer. The median value before health education was 65, after being given health education was 95. The results of the analysis obtained a value of Z-2.065, p value 0.039. The conclusion of counseling is useful to increase the knowledge of elementary school students about menarche